Sistem Pemantauan Kelembaban Tanah Jarak Jauh Berbasis LoRa Menggunakan Sensor pH dan Kelembaban - Gani, Mina Naidah; Hepi Ludiyati; Rifa Hanifatunnisa; Eril Mozef; Rizqa Nur Ananti (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2023)
This study focuses on the pivotal role of water and soil in agriculture, emphasizing their significance for photosynthesis and as a planting medium, respectively. Maintaining uncontaminated soil is crucial for optimal crop growth. Remote monitoring of soil quality is facilitated by LoRa technology, with a microcontroller system employing sensors for soil moisture and pH. YL-69 moisture sensors exhibit an average error of 0.077%, with a range from 0% to 0.016%, while pH electrode probe sensors register an average error of 0.0288%, ranging from 0.034% to 0.021%. The monitoring data is transmitted through the LoRa network connected to ESP32. Field testing under Line-of-Sight (LOS) conditions at a maximum distance of 500 meters and Non-Line-of-Sight (NLOS) conditions up to 50 meters reveals that the gateway successfully detects RSSI values (-104 dBm to -64 dBm) and SNR values (-2dB to +10dB) within acceptable ranges. The average delay during data transmission between the node and the gateway is measured at 2.118 seconds. This research demonstrates the effectiveness of LoRa technology in remotely monitoring and transmitting crucial soil parameters, providing valuable insights for precision agriculture.